Tethered balloon measurements during Arctic spring conditions in Ny-Ålesund in the framework of HALO-(AC)3 - Lonardi, M.; Ehrlich, A.; Müller, J.; Saavedra Garfias, P.; Wendisch, M. (Universität Leipzig, 2023)
The tethered balloon system BELUGA (BalloonbornE moduLar Utility for profilinG the lower Atmosphere) was operated in spring 2022 at the AWIPEV research station (Ny-Ålesund, Svalbard). In-situ profiles of thermodynamic parameters, thermalinfrared radiation, aerosol particle concentrations, and turbulence, were measured and analyzed. Additionally, samples of ice-nucleating particles were collected at various heights. In combination with previous BELUGA datasets, measurements from this campaign provide a solid base for studying the vertical profiles of the radiative energy budget and heating rates in different atmospheric states in the Arctic lower troposphere. Here, example thermal-infrared radiation profiles are presented for a period of persisting cloudless conditions related to a series of marine cold air outbreaks in late March/early April. Measurements in clouds are analyzed for a developing cloud observed on 6 May and display the impact of cloudiness on radiation profiles. Das Fesselballonsystem BELUGA (BalloonbornE moduLar Utility for profilinG the lowerAtmosphere) wurde im Frühjahr 2022 an der Forschungsstation AWIPEVStation (Ny-Ålesund, Svalbard) eingesetzt. In-situ-Profile von thermodynamischen Parametern, terrestrische Strahlung, Aerosolpartikelkonzentrationen und Turbulenz wurden gemessen und ausgewertet. Zusätzlich wurden in verschiedenen Höhen Proben von eiskeimbildenden Partikeln gesammelt. In Kombination mit früheren BELUGA Messungen zu anderen Jahreszeiten und an anderen arktischen Messstandorten bieten die Messungen in Ny-Ålesund eine Grundlage fürweitereUntersuchungen des Strahlungsenergiehaushalts und des Einflusses vonWolken auf atmosphärische Heizraten. Profile der Strahlungsbilanz werden für eine anhaltende Kälteperiode zwischen Ende März bis Anfang April 2022 vorgestellt. Über diesen Zeitraum herrschten vor allem wolkenlose Bedingungen. Weitere Beobachtungen unter einer sich entwickelnden Wolkendecke am 6. Mai 2022 zeigen den Einfluss der Bewölkung auf die Strahlungsprofile.